A case study on the influence of violent cartoon shows on children's play behavior - Verzola. Lesley Ann D.; Trio, Consuelo Q. (2004.)
This study sought to find-out the influence of violent cartoon shows commonly watched by preschool children in La Escuela Del Nino Jesus in Marikina City to their play behavior. The research aimed to analyze the viewing patterns of selected preschool children in relation to violent cartoon shows, describe the content of the cartoon shows commonly watched by children, and determine the display of aggressive behavior and use of foul language of children during playtime. Necessary data for the study were gathered by means of interview to parents; and observation (both on the cartoon shows their children watch regularly. They were also given checklists to record (for two weeks) the cartoon shows they watched and the time they watched it. The researcher watched the same cartoon shows that the children watched and record the aggressive behavior displayed and the foul language used by the characters. Also, the researcher observed the children in the classroom during their playtime and recorded the aggressive behavior they displayed. Data in this case study were merely descriptive. Analysis of the cartoon shows focused on two cartoons which shows which were most commonly watched by the 10 children observed. The observation was done for two consecutive weeks.results of the study showed that the aggressive behavior and use of foul language displayed by the characters in the cartoon shows were imitated by children during play but not at all times. Some behavior displayed by the children did not come from the cartoon shows they just watched. There are other factors which can influence a child's behavior like: the lack of guidance of an adult, the number of hours child is exposed to TV, the types of programs watched, and the influence of parents, peers, and other members of the household and/or the neighborhood. The implications of this study are that further research must be conducted to explore the impact of both safe and unsafe programs in children's television on their behavior and attitude. Recommendations and applications of the study were provided at the last part of the research.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Television and children -- Philippines -- Psychological aspects -- Case study; Violence and mass media -- Case study